A comparative study of continuous wave and pulsed wave Coz lazer cutting of a polymer matrix composite material - Mohd Razali, Mohamad (2005)
Heat affected zone (HAZ) is always produced when laser cutting is used to cut any material. In this paper, a comparative study of the effects of continuous wave (CW) and pulsed wave (PW) C02 laser cutting on generation of HAZ is presented. The material used in the cutting experiment is Kevlar which is a widely used polymer matrix composite (PMC). The thickness of the Kevlar sheet considered in the present study is 2 mm. The effects of two main laser cutting parameters i.e. the laser power output and the cutting speed on the generation of HAZ are investigated in the study. The results showed that PW laser gives a smaller area of HAZ as compared to the